2022
DOI: 10.3390/biom12081108
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation

Abstract: Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson’s disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…In contrast, in this study, we revealed that the accumulation of αSyn in the cytosol and nucleus could result in distinct cytotoxicities in MEF. Several studies have reported that the presence of αSyn in the nucleus of cells may underlie αSyn-derived neurodegeneration [6][7][8][9]. We demonstrated that the nucleus-localized αSyn promoted similar cytotoxicity as described in previous studies [7][8][9], and was related to the abnormal rRNA processing and elevated ribosomal protein in this study (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, in this study, we revealed that the accumulation of αSyn in the cytosol and nucleus could result in distinct cytotoxicities in MEF. Several studies have reported that the presence of αSyn in the nucleus of cells may underlie αSyn-derived neurodegeneration [6][7][8][9]. We demonstrated that the nucleus-localized αSyn promoted similar cytotoxicity as described in previous studies [7][8][9], and was related to the abnormal rRNA processing and elevated ribosomal protein in this study (Figure 8).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have reported that the presence of αSyn in the nucleus of cells may underlie αSyn-derived neurodegeneration [6][7][8][9]. We demonstrated that the nucleus-localized αSyn promoted similar cytotoxicity as described in previous studies [7][8][9], and was related to the abnormal rRNA processing and elevated ribosomal protein in this study (Figure 8). Thus, the neurotoxicity of nuclear αSyn might be mediated via ribosomal biogenesis, and the accumulated cytosolic αSyn would propagate the spread of alpha-synucleinopathy and neuroinflammation by the disruption of autophagy-lysosomal degradation pathway.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the case of RNAi-knockdown, floating cells were transfected with Lipofectamine ™ RNAiMAX (Thermofisher Scientific, Grand Island, New York, NK, USA) and medium was changed the next day. To separate nuclear and cytosolic proteins, cells were homogenized and fractionated as previously described [48].…”
Section: Nuclear and Cytoplasmic Separation Of Proteinmentioning
confidence: 99%
“…Besides phosphorylation, SUMOylation, which is generated by mature small ubiquitin-related modifiers (SUMO), may occur during the nuclear translocation of αS [ 58 ]. Interestingly, distinct αS species translocate from the nucleus to neuronal processes during neuronal differentiation, which suggests that the maturation process of the nervous system may affect subcellular localization [ 59 ]. With respect to protein conformational change and aggregation, exposure to human fibrotic αS seed facilitates the formation of intranuclear inclusions in mouse primary cortical neurons [ 60 ].…”
Section: Interaction Between αS and Epigenetic Factorsmentioning
confidence: 99%